Somatic differentiation in professional school pupils expressed according to Wanke’s typology - Henicz, Tadeusz (Anthropological Review, 1976)
The study concerned 171 pupils, examined during 3 years from 1968 to 1971, aged 17 years and 5 months to 18 years and 2 months. The classification of somatic types was applied according to A. Wanke (Przegląd Antropologiczny — Anthropological Review vol. 20 pages 64-104 Poznań 1954). Summing up the resulting statistics the author concludes that: 1. In the tested team the number of element I increases with age; 2. The number of element H decreases with age; 3. The number of elements A and V are similar and remain on the same level; 4. The growth of clement I is accompanied by a lessening of element H and inversely; 5. In the group less engaged in manual work element I occurs more frequently; 6. In the older age groups of the team more strongly engaged in manual work, element V occurs more frequently.